2022
DOI: 10.1101/2022.02.11.22270611
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Long-term antibody response to SARS-CoV-2 in children

Abstract: Almost two years into the pandemic and with vaccination of children significantly lagging behind adults, long-term pediatric humoral immune responses to SARS-CoV-2 are understudied. The C19.CHILD Hamburg (COVID-19 Child Health Investigation of Latent Disease) Study is a prospective cohort study designed to identify and follow up children and their household contacts infected in the early 2020 first wave of SARS-CoV-2 infections. We screened 6113 children <18 years by nasopharyngeal swab-PCR in a low-inciden… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 56 publications
(64 reference statements)
0
7
0
Order By: Relevance
“…A recent study showed that children and adults retain both anti-S IgG and anti-N antibodies until 9 months post symptom onset. 23 Similarly, other studies demonstrated detectable IgG and Nabs in children with asymptomatic or mildly symptomatic infection for at least 6 months following symptom onset, [24][25][26] while one study reported that children with asymptomatic or mildly symptomatic COVID-19 mount a robust antibody response with a low but detectable memory B-and T-cell response and is stable up to 12 months post-infection. 27 Although antibody levels gradually decrease over time, antibody responses are still sustained at least 6 months post-infection.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…A recent study showed that children and adults retain both anti-S IgG and anti-N antibodies until 9 months post symptom onset. 23 Similarly, other studies demonstrated detectable IgG and Nabs in children with asymptomatic or mildly symptomatic infection for at least 6 months following symptom onset, [24][25][26] while one study reported that children with asymptomatic or mildly symptomatic COVID-19 mount a robust antibody response with a low but detectable memory B-and T-cell response and is stable up to 12 months post-infection. 27 Although antibody levels gradually decrease over time, antibody responses are still sustained at least 6 months post-infection.…”
Section: Discussionmentioning
confidence: 95%
“…It has been reported that younger symptomatic children have higher anti-S IgG and Nabs in comparison to older children, adolescents and young adults. 16,23,33,34 Other studies demonstrated higher anti-SARS-CoV-2 IgG, but lower Nabs or similar anti-S IgG in children compared with adults, 35–37 while one recent study revealed that Nabs were lower in children compared with adults early after infection, but they were similar by 6 weeks post-infection. 17 Additionally, it has been indicated that children with asymptomatic SARS-CoV-2 infection are able to mount a robust and durable immune response similar to adults.…”
Section: Discussionmentioning
confidence: 99%
“…35 As the pandemic progresses and more studies are developed, there is evidence of a lower incidence of the disease in children. 36 There is enough evidence that the new coronavirus has a unique mechanism of interaction with the host. More studies are essential to fill the knowledge gap about children's immune response to SARS-CoV-2 and to better understand the relationship between chronic diseases, such as caries, and the new coronavirus.…”
Section: The Available Data Indicate a Low Incidence Of Covid-19 Amon...mentioning
confidence: 99%
“…Several studies reported on duration of persistence of antibodies after a SARS-CoV-2 infection in children and adolescents. Some studies reported that anti-spike IgG levels decrease within 4 to 6 months [40,41], whereas others showed that they remained detectable up to 9 to 18 months [9,42,43].…”
Section: Participant Characteristicsmentioning
confidence: 99%
“…Our findings show that the overall humoral and population immunity is high in children and adolescents in Switzerland. Policy makers and healthcare professionals in Switzerland closely followed our study and considered these findings to guide their decisions on public health The Ciao Corona study is unique and one of few large longitudinal studies in youth [9,37,43].…”
Section: Participant Characteristicsmentioning
confidence: 99%